Valor nutritivo de rações para ovinos com quatro níveis do resíduo de panificação - Oliveira, Alexsandro Holanda de (2005)
The research objectified to test rations, (50% concentrate and 50% forrage), utilize different levels of substituition of corn for waste bakery (WB), in the concentrate.16 males sheeps were used without defined race and weigtht live between 18,5 and 26,5 kg. The experimental period had duration of 21 days, being 14 days for adptation and 7 days for collections of samples. The used experimental delineament was it entirely casuality with 4 treatments (levels of substituition of corn for remainder bakery in the concentrate 20,0;40,0;60,0 e 80,0%), each one with 4 repetitions. Significant differences were not observed among the treatments in the appraised produtive parameters ( it test of Tukey P>0,05), digestibility of dry matter (DM), crude protein (CP), organic matter (OM), ether extract (E.E), gross energy (GE), fyber on neutral detergent (FND). The remainder of bakery can be utilize in 80% of substituition the corn in rations to sheeps in the stage of termination, each the relacion forrage: concentrate of 50:50.